Distribution of persistent organic pollutants (POPS) IN wild Bluefin tuna (Thunnus thynnus) from different FAO capture zones. (June 2016) - Chiesa, L.M.; Labella, G.F.; Panseri, S.; Pavlovic, R.; Bonacci, S.; Arioli, F.
Abstract: Residues of environmental contaminants in food represent a concern in food safety programs. In this study, the distribution of persistent organic pollutants (POPs) were evaluated in 79 tuna samples from FAO areas 51 (Indian Ocean), 71 (Pacific Ocean), 34 (Atlantic Ocean), and 37 (Mediterranean Sea). 6 polychlorinated biphenyls (PCBs), 16 organochlorines (OCs) and 7 polybrominated biphenyl ethers (PBDEs) were selected as representative compounds according to EFSA POPs monitoring guidelines. An analytical method, based on Accelerated Solvent Extraction (ASE), with an "in-line" clean-up step and GC-MS/MS detection, was developed, validated and applied. PCBs were detected in all FAO areas, with a prevalence of 100% for most of them. In the FAO area 37, only, all PBDEs were detected. Only 5 OCs were detected. The results showed that POPs contamination of tuna reflects FAO area contamination; in particular FAO area 37 was the most polluted. Moreover, tuna muscle was an appropriate matrix for monitoring contamination and for obtaining information about food safety. Graphical abstract: Profiles of detected POPs in tuna samples from different FAO zones. Highlights: The POPs contamination of Bluefin tuna is strictly related to its FAO catch area. Control of POPs in fish is essential to asses human exposure to contaminants through the diet. ASE method with an "in line" clean up represent an interesting approach for POPs routine analysis. Polybromodiphenyl ethers (PBDE) were detected in tuna form Mediterranean Sea as emerging POPs.